Developmental changes and sex differences in DNA methylation and demethylation in hypothalamic regions of the mouse brain - Carla D. Cisternas; Laura R. Cortes; Emily C. Bruggeman; Bing Yao; Nancy G. Forger (Epigenetics, 2020)
DNA methylation is dynamically modulated during postnatal brain development, and plays a key role in neuronal lineage commitment. This epigenetic mark has also recently been implicated in the development of neural sex differences, many of which are found in the hypothalamus. The level of DNA methylation depends on a balance between the placement of methyl marks by DNA methyltransferases (Dnmts) and their removal, which is catalyzed by ten-eleven translocation (Tet) methylcytosine dioxygenases. Here, we examined developmental changes and sex differences in the expression of Tet and Dnmt enzymes from birth to adulthood in two hypothalamic regions (the preoptic area and ventromedial nucleus) and the hippocampus of mice. We found highest expression of all Tet enzymes (Tet1, Tet2, Tet3) and Dnmts (Dnmt1, Dnmt3a, Dnmt3b) in newborns, despite the fact that global methylation and hydroxymethylation were at their lowest levels at birth. Expression of the Dnmt co-activator, Dnmt3l, followed a pattern opposite to that of the canonical Dnmts (i.e., was very low in newborns and increased with age). Tet enzyme activity was much higher at birth than at weaning in both the hypothalamus and hippocampus, mirroring developmental changes in gene expression. Sex differences in Tet enzyme expression were seen in all brain regions examined during the first week of life, whereas Dnmt expression was more balanced between the sexes. Neonatal testosterone treatment of females only partially masculinized enzyme expression. Thus, Tet expression and activity are elevated during neonatal brain development, and may play important roles in sexual differentiation of the brain.